2011
DOI: 10.1161/hypertensionaha.110.160796
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Heart, Myocardial Fibrosis, and its Relationship to Circulating C-Type Natriuretic Peptide

Abstract: Myocardial aging is characterized by LV fibrosis leading to diastolic and systolic dysfunction. Studies have established the potent anti-fibrotic and anti-proliferative properties of C-type natriuretic peptide (CNP), however the relationship between circulating CNP, LV fibrosis and associated changes in LV function with natural aging are undefined. Accordingly, we characterized the relationship of plasma CNP with LV fibrosis and function in 2, 11 and 20 month old male Fischer rats. Further in vitro, we establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
91
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 45 publications
9
91
0
2
Order By: Relevance
“…The cGMP‐dependent signaling appears to be central for antifibrotic effects of CNP 88, 90. Evidence from Burnett's laboratory suggests that a non‐cGMP‐dependent pathway also mediates the antifibrotic effects of CNP 78. In conclusion, antifibrotic and ‐hypertrophic effects of CNP appear to be mediated both by activation of NPRB and by a non‐cGMP‐dependent mechanism, whereas blood‐pressure–lowering effect of CNP is not dependent on activation of NPRB.…”
Section: Cnp In the Diseased Heartmentioning
confidence: 88%
See 1 more Smart Citation
“…The cGMP‐dependent signaling appears to be central for antifibrotic effects of CNP 88, 90. Evidence from Burnett's laboratory suggests that a non‐cGMP‐dependent pathway also mediates the antifibrotic effects of CNP 78. In conclusion, antifibrotic and ‐hypertrophic effects of CNP appear to be mediated both by activation of NPRB and by a non‐cGMP‐dependent mechanism, whereas blood‐pressure–lowering effect of CNP is not dependent on activation of NPRB.…”
Section: Cnp In the Diseased Heartmentioning
confidence: 88%
“…However, plasma levels of CNP are very low even in patients with severe HF. Levels of circulating CNP actually appear to decrease in rats during aging, and this correlates with an increase in cardiac fibrosis 78. In addition to the heart, head and neck tissue are important sources of CNP 79…”
Section: Cnp In the Diseased Heartmentioning
confidence: 99%
“…We recently demonstrated that a progressive decline in circulating CNP characterizes natural aging and is strongly associated with a reciprocal increase in cardiac fibrosis which preceded cardiac dysfunction (29). Although CNP lacks natriuretic and diuretic activity, CNP may have important renal-protective properties which serve to maintain renal structure and function, such as inhibition of glomerular fibrosis after renal injury (4).…”
mentioning
confidence: 99%
“…We also hypothesized that age-related increases in urinary CNP precedes an elevation in proteinuria. To address these hypotheses, we assessed circulating and urinary CNP in a Fischer rat model of experimental aging, which is equivalent to human aging from adolescence to the six decade of life (29), and also determined renal structural and functional adaptations to the aging process. Finally, we investigated the presence and localization of CNP by immunohistochemistry in the kidneys of young and old, healthy human kidney donors.…”
mentioning
confidence: 99%
“…[41] The increased wall thickness is accompanied by decreased cardiomyocyte count and increased left ventricular collagen content, which are features of fibrosis. [42] Animal studies have demonstrated left ventricular collagen content increases linearly with age but can increase two-fold during the later years of life. [42] Overall, the cumulative impact of decreased cardiomyocyte count, increased collagen deposition and increased stiffness leads to significant ventricular dysfunction which is a major characteristic of the aging heart.…”
Section: Changes In Ventricle Structurementioning
confidence: 99%